Analysis of corrosion fatigue for commercially pure titanium using nitrogen ion implantation - Ali, Nurdin (2014)
The objective of this research is to determine the corrosion fatigue behaviours for commercially pure titanium (CpTi) using nitrogen ion implantation. A series of studies was conducted to obtain the mechanical properties, corrosion resistance and fatigue and corrosion fatigue behaviours and to develop model prediction of corrosion fatigue life of nitrogen ion implanted CpTi (Nii-Ti). Initially, nine specimens of CpTi were implanted nitrogen ion with the energy of 80, 100 and 115 keV and dose of 0.5x1017, 1.0x1017 and 2.0x1017ions/cm2 to characterize its surface properties and to obtain corrosion resistance. The result shows that energy of 100 keV and dose of 2.0x1017ions/cm2 was the optimal implanted parameter. In the second study, fatigue and corrosion fatigue test were performed to investigate the fatigue and corrosion fatigue behaviours. The fatigue specimens were implanted with the energy of 100 keV and dose of 2.0x1017ions/cm2 . The fatigue tests were carried out for Nii-Ti specimens in saline solution and for CpTi and Nii-Ti specimens in laboratory air by means of axial loading condition at stress level between 240 and 320 MPa. The results were nitrogen ion implantation improved slightly the fatigue life of CpTi and Nii-Ti with the fatigue strength of 250 MPa and 260 MPa, respectively. Finally, the prediction of corrosion fatigue life was developed based on corrosion pit growth law. The stress amplitudes of 250, 260 and 280 MPa were selected to measure penetration rate of specimens at various elapsed times using electrochemical method in saline solution, then established the empirical model. The result shows that the expression fits the experimental data well. In conclusion, the effects of nitrogen ion implantation on surface properties and adhesion strength of nitride layers improved the fatigue and corrosion fatigue life of Nii-Ti.